Management of Multiple Renal Arteries and Unusual Venous Anatomy During Kidney Transplant: From a Simple Technical Problem to a Graft-Saving Procedure - Popov, Zivko; Oliver Stankov; Sotir Stavridis; Skender Saidi; Ognen Ivanovski; Goce Spasovski; Koco Cakalaroski; Ninoslav Ivanovski (Baskent University, 2020)
Incidence of vascular anomalies in donor kidneys varies from 18% to 30% and presents a challenge for a transplant surgeon in kidney transplant. Here we present our personal experience for man - agement of the complicated and unexpected cases.